2021
DOI: 10.1111/mec.15991
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of foot‐and‐mouth disease virus serotype O dispersal and associated drivers in East Africa

Abstract: The continued endemicity of foot and mouth disease virus (FMDV) in East Africa has significant implications for livestock production and poverty reduction, yet its complex epidemiology in endemic settings remains poorly understood. Identifying FMDV dispersal routes and drivers of transmission is key to improved control strategies. Environmental heterogeneity and anthropogenic drivers (e.g., demand for animal products) can impact viral spread by influencing host movements. Here, we utilized FMDV serotype O VP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In addition, pastoral cattle herds, herds in areas of low rainfall, and herds in areas of high cattle density had relatively higher numbers of seropositive animals. The phylogeographic modeling of sequences obtained from the same cross-sectional study, combined with previous sequence data from Uganda, Kenya, Tanzania, and Ethiopia, re-affirmed the transboundary nature of the spatiotemporal spread of FMDV and identified a tendency for FMDV to remain circulating near livestock markets, in areas of high cattle density, and in areas of high human population density [ 10 ]. However, using available methods, no directional trends in FMDV spread were elucidated.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, pastoral cattle herds, herds in areas of low rainfall, and herds in areas of high cattle density had relatively higher numbers of seropositive animals. The phylogeographic modeling of sequences obtained from the same cross-sectional study, combined with previous sequence data from Uganda, Kenya, Tanzania, and Ethiopia, re-affirmed the transboundary nature of the spatiotemporal spread of FMDV and identified a tendency for FMDV to remain circulating near livestock markets, in areas of high cattle density, and in areas of high human population density [ 10 ]. However, using available methods, no directional trends in FMDV spread were elucidated.…”
Section: Introductionmentioning
confidence: 77%
“…In a previous study of FMDV phylogenetics using seraphim , we identified several characteristics of areas where FMDV is likely to remain circulating (near livestock markets, areas of high cattle density, and high human population density), but we were unable to elucidate directional patterns in FMDV spread [ 10 ]. Using the RGF model, we identified directional trends related to rainfall, cattle density, and proximity to livestock markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMD outbreaks were linked to areas in which livestock markets operate or that are close to human consumption centres as evidenced by a link to the location of abattoirs and high human density locations. A growing body of evidence of viral circulation across cattle markets, highly populated areas and slaughterhouses backs up this epidemiological linkage (Buckle et al., 2021 ; Colenutt et al., 2022 ; Di Nardo et al., 2021 ; Gunasekara et al., 2021 ; Munsey et al., 2021 ). Cross‐border trade was also represented and was often connected to a higher outbreak risk.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreak risk attributed to presumed contact with wildlife was confirmed in some models, although further investigations are required. Di Nardo et al, 2021;Gunasekara et al, 2021;Munsey et al, 2021).…”
Section: Animal Demographics and Livestock-wildlife Interactionsmentioning
confidence: 99%